Pengaruh Kecukupan Modal, Likuiditas, Efisiensi Operasional Dan Return On Asset Terhadap Earning Per Share Pada Perbankan Bumn Periode 2012 – 2021 - Andriyani Andriyani (Science of Management and Students Research Journal (SMS), 2022)
The aims of this study are as follows: 1.) To determine and analyze the effect of Capital Adequacy, Liquidity, Operational Efficiency and Return On Assets simultaneously on Earning Per Share in BUMN Banking for the 2012-2021 period. 2.) To determine and analyze the effect of Adequacy Capital, Liquidity, Operational Efficiency and Return On Assets partially on Earning Per Share in BUMN Banking for the 2012-2021 Period. The type of data needed and collected in this study is secondary data. The source of data used in this research is from the annual report through the official website https://www.bni.co.id, https://www.bri.co.id, https://www.btn .co.id, https://www.mandiri.co.id. the results of multiple regression analysis with panel data can be obtained regression equation model Y = 8,696 + 0,091 + 2,219 + 1,001 + 0,607 + e. The value of R Square is 0.711, which means that the contribution of the independent variables, namely Capital Adequacy, Liquidity, Operational Efficiency and Return On Assets affects the Earning Per Share variable by 71.1%, while the remaining 28.9% is influenced by other variables outside the study. this. There is a significant positive effect between Capital Adequacy, Liquidity, Operational Efficiency and Return On Assets together (simultaneously) on Earning Per Share in BUMN Banking for the 2012-2021 period. Capital Adequacy and Operational Efficiency have no partial significant effect on Earning Per Share . Liquidity and Return On Assets have a partial significant effect on Earning Per Share.